Internet of Things, Smart Spaces, and Next Generation Networks and Systems: 21st International Conference, NEW2AN 2021, and 14th Conference, ruSMART 2021, St. Petersburg, Russia, August 26-27, 2021, Proceedings - Koucheryavy, Yevgeni; Balandin, Sergey; Andreev, Sergey (Lecture Notes in Computer Science, 2022)
This book constitutes the joint refereed proceedings of the 21st International Conference on Next Generation Teletraffic and Wired/Wireless Advanced Networks and Systems, NEW2AN 2021, and the 14th Conference on Internet of Things and Smart Spaces, ruSMART 2021. The conference was held virtually due to the COVID-19 pandemic.The 41 revised full papers presented were carefully reviewed and selected from 118 submissions.